2015
DOI: 10.1016/j.alit.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhaled corticosteroids on bronchial asthma in Japanese athletes

Abstract: These data suggest that ICS is effective for asthma in most athletes. However, certain asthmatic athletes are less responsive to ICS than expected. The pathogenesis in these subjects may differ from that of conventional asthma characterized by chronic allergic airway inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…However, 15% of athletes only showed a minimal response to ICS. 139 Heterogeneity of asthma phenotypes in the athlete population 132,140-142 probably explains why not all asthmatic athletes respond to ICS. Indeed, many athletes have little or no evidence of eosinophilic airway inflammation, 76,143,144 and therefore may not benefit as much from ICS as other individuals with eosinophilic asthma.…”
Section: Prevention Of Exercise-induced Bronchoconstriction In Athletesmentioning
confidence: 99%
“…However, 15% of athletes only showed a minimal response to ICS. 139 Heterogeneity of asthma phenotypes in the athlete population 132,140-142 probably explains why not all asthmatic athletes respond to ICS. Indeed, many athletes have little or no evidence of eosinophilic airway inflammation, 76,143,144 and therefore may not benefit as much from ICS as other individuals with eosinophilic asthma.…”
Section: Prevention Of Exercise-induced Bronchoconstriction In Athletesmentioning
confidence: 99%
“…Doses of inhaled glucocorticosteroids are determined by the degree of symptoms severity. Daily doses of in- [45].…”
Section: Medical History Datamentioning
confidence: 99%
“…Occasionally, for various reasons, inhaled glucocorticosteroids are less effective in asthma control in competitive athletes. Hoshino et al reported ineffectiveness of therapy with inhaled glucocorticosteroids in 16.3% of 80 asthmatic athletes [45].…”
Section: Treatmentmentioning
confidence: 99%